2017
DOI: 10.5483/bmbrep.2017.50.11.174
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of selenocysteine on replicative senescence in human adipose-derived mesenchymal stem cells

Abstract: In most clinical applications, human mesenchymal stem cells (hMSCs) are expanded in large scale before their administration. Prolonged culture in vitro results in cellular senescence-associated phenotypes, including accumulation of reactive oxygen species (ROS) and decreased cell viabilities. Profiling of stem cell-related genes during in vitro expansion revealed that numerous canonical pathways were significantly changed. To determine the effect of selenocysteine (Sec), a rare amino acid found in several anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Treatment with physiological doses of selenocysteine (50 and 100 nM) of adipose tissue-derived mesenchymal stem cells significantly increased cell survival and down-regulated prooxidant and proinflammatory pathways, thus possessing a protective effect on replicative senescence of adipose tissue-derived mesenchymal stem cells. These effects were accompanied by differential selenoprotein response characterized by up-regulation of GPX1 and reduced SELENOO and MSRB1 expressions [112].…”
Section: Se In Adipogenesis and Adipocyte Signaling Pathwaysmentioning
confidence: 99%
“…Treatment with physiological doses of selenocysteine (50 and 100 nM) of adipose tissue-derived mesenchymal stem cells significantly increased cell survival and down-regulated prooxidant and proinflammatory pathways, thus possessing a protective effect on replicative senescence of adipose tissue-derived mesenchymal stem cells. These effects were accompanied by differential selenoprotein response characterized by up-regulation of GPX1 and reduced SELENOO and MSRB1 expressions [112].…”
Section: Se In Adipogenesis and Adipocyte Signaling Pathwaysmentioning
confidence: 99%
“…In particular, disturbance stem cell redox homeostasis by excessive production of reactive oxygen species (ROS) could lead to oxidative stress, resulting in stem cell dysfunctions such as stem cell senescence and lost stemness during long-term in vitro expansion [14, 17]. Moreover, it has been shown that ADSCs also undergo accumulation of ROS in large scale in vitro expansion [18], and precise regulation of ROS is crucial for cellular homeostasis of ADSCs [19]. Under physiological conditions, stem cells maintain low levels of ROS to preserve their stemness and to remain quiescent in mammals [14, 15, 20].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic implications of SOD3 in various skin diseases such as psoriasis and atopic dermatitis have been well-studied. It has previously been shown that treatment with antioxidants can enhance the survival and therapeutic efficacy of MSCs ( 20 , 21 , 22 ). Similarly, MSCs were found to promote cerebellar neuronal survival through the secretion of SOD3 ( 23 ).…”
Section: Introductionmentioning
confidence: 99%